2010
DOI: 10.1089/jmf.2010.1021
|View full text |Cite
|
Sign up to set email alerts
|

Phenolic-Containing Organic Extracts of Mulberry (Morus alba L.) Leaves Inhibit HepG2 Hepatoma Cells Through G2/M Phase Arrest, Induction of Apoptosis, and Inhibition of Topoisomerase IIα Activity

Abstract: The entire plant of Morus alba L. (Family Moraceae), or mulberry, possesses medical benefits, including anticancer properties. In this study, we investigated the effect of mulberry leaf extracts on the human hepatoma HepG2 cell line, which is related to hepatocellular carcinoma. Mulberry leaf extracts were prepared using four solvents, each with different polarities: 100% methanol (MeOH), 50% aqueous MeOH, 1-butanol (BuOH), and hot water (W). The phenolic profile, total polyphenol content, antioxidant capacity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
68
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 97 publications
(82 citation statements)
references
References 40 publications
8
68
2
Order By: Relevance
“…Therefore, the decrease in Bax or active caspase-3 expression and increase in Bcl-2 expression can provide a neuroprotective effect by inhibiting Aβ-induced apoptosis. For example, organic extracts of mulberry leaves containing mainly phenolic compounds, including chlorogenic acid, inhibited apoptosis in HepG2 hepatoma cells by arresting the cell cycle in the G2/M phase (Granado-Serrano et al, 2007;Naowaratwattana et al, 2010). In addition, chlorogenic acid exhibited an anti-apoptotic effect on methylglyoxyal-induced neuroblastoma cell apoptosis (Neuro-2A cells) (Huang et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the decrease in Bax or active caspase-3 expression and increase in Bcl-2 expression can provide a neuroprotective effect by inhibiting Aβ-induced apoptosis. For example, organic extracts of mulberry leaves containing mainly phenolic compounds, including chlorogenic acid, inhibited apoptosis in HepG2 hepatoma cells by arresting the cell cycle in the G2/M phase (Granado-Serrano et al, 2007;Naowaratwattana et al, 2010). In addition, chlorogenic acid exhibited an anti-apoptotic effect on methylglyoxyal-induced neuroblastoma cell apoptosis (Neuro-2A cells) (Huang et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…21 M. rubra is one of the most important species of the genus Morus, with fruits having substantial levels of phenolics, anthocyanins, carotenoids and ascorbic acid. 3 Many studies have investigated the cytotoxic effects of different berry species, [8][9][10] however to the authors' best knowledge there is no study reporting cytotoxic effect of M. rubra in the literature. It is adviced that in vitro experiments are helpful and advisor for determining first biological effect of a natural or syntetic product.…”
Section: Discussionmentioning
confidence: 99%
“…Hovewer, higher extract concentrations which cause an arrest of cells at the G 2 /M phase of the cell cycle and modify microtubule organization, 35 while Naowaratwattana et al reported that M. alba leaf extract inhibits the proliferation of HepG2 cells in a dose-dependent manner by inducing cell cycle arrest at G 2 /M phase, caspase activity and inhibiting topoisomerase IIα activity. 9 Recently, Kollar et al reported that prenylated flavonoids from Morus alba inhibit the growth of human monocytic leukemia (THP-1) cells through inducing G 1 cell cycle arrest and apoptotic pathway. 36 We determined that AMRE induced cell cycle arrest at G 0 /G 1 phase in both A549 and PC-3 cells in a concentration dependent manner.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Anti-microbial properties have been described by previous science fair investigators from some natural extracts, and the majority of these studies focus on crude extracts [9] . Morus species have been a rich food source, and the leaf extracts of Morus Alba (M. alba) are used for anticancer and antioxidants properties [10,11] . Bombax seeds are useful for treating gonorrhea and chronic cystitis, bark for improving skin color, flowers for making tea and silk for cotton production.…”
Section: Introductionmentioning
confidence: 99%